Korelasi Kuat Tekan Bebas dengan Kuat Geser Langsung pada Tanah Lempung yang dicampur dengan Zeolit - Hermawan, M. Iqbal; Afriani, Lusmeilia; Iswan, Iswan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This research was conducted to determine the effect between zeolite and clay of compressivestrength and shear strength. Construction founded on clay will cause some impact, such as lack ofcompressive strength and shear strength. Therefore, before the construction of structures on theclay, the clay must be stabilized first. In this research, soil stabilization using zeolite.Based on the results of this research there was an increase in the compressive strength of clay by94,5 % from 0,2975 kg/cm 2 be 0,5787 kg/cm 2 , and improving the clay cohesion of 54,17 % from0.24 kg/cm 2 be 0,36 kg/cm 2 , and the increase in the maximum shear strength of 43,89 % of 0.4754kg/cm 2 be 0,6841 kg/cm 2 , the additon of zeolite until 10%. From these values it can be concluded,compressive strength and shear strength increases as a percentage addition of zeolite, althoughthe increase that occurred in the unconfined compressive strength and direct shear strength is notas great.Keywords : Clay, Zeolite, Uncofined Compressive Strenght, Shear Strenght